2022
DOI: 10.1212/wnl.0000000000200273
|View full text |Cite
|
Sign up to set email alerts
|

Connectomic Profiles and Cognitive Trajectories After Epilepsy Surgery in Children

Abstract: Objective:Neurocognitive outcomes following surgery for temporal lobe epilepsy in childhood are variable. Postoperative changes are not directly predicted by seizure-freedom and associations between epilepsy, neuropsychological function, and developing neural networks are poorly understood. Here, we leveraged whole-brain connectomic profiling in magnetoencephalography (MEG) to retrospectively study associations between brain connectivity and neuropsychological function in children with temporal lobe epilepsy u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…This may reflect a narrowing of a normally widely distributed cognitive network underlying working memory functioning. Recent research has shown that theta connectivity in specific edges were correlated negatively to working memory in paediatric temporal lobe epilepsy 90 supporting our observation that alterations in typical patterns of theta activity may interfere with working memory function in children with neurological disease. Theta modularity may represent a sensitive measure to detect differences in working memory in PAE 5, 82 .…”
Section: Discussionsupporting
confidence: 90%
“…This may reflect a narrowing of a normally widely distributed cognitive network underlying working memory functioning. Recent research has shown that theta connectivity in specific edges were correlated negatively to working memory in paediatric temporal lobe epilepsy 90 supporting our observation that alterations in typical patterns of theta activity may interfere with working memory function in children with neurological disease. Theta modularity may represent a sensitive measure to detect differences in working memory in PAE 5, 82 .…”
Section: Discussionsupporting
confidence: 90%
“… 59 Patients with lower neuropsychological functioning at the time of preoperative assessment (most probably attributable to earlier age of epilepsy onset and longer duration of epilepsy) were more likely to improve from pre- to postoperative neuropsychological assessment. This ‘catch-up’ effect in functioning could be driven by postoperative structural 17 , 26 and functional 67 brain plasticity. At the same time, one might argue that patients with the highest neuropsychological functioning at the time of preoperative assessment have ‘the most to lose’, as previously proposed.…”
Section: Discussionmentioning
confidence: 99%
“…It is showed that by the application of connectomes, the result of epileptic-surgery can be recovered plus threats of post op neuro cognitive sequelae, with cognitive impairment (CI), cognitive dementia (CD), memory, language and semantic weakening, verbal linguistic problems can be concentrated. [53][54][55][56] Finally, NBC is largely applied in neuromodulation, mainly conventional open as well as closed loop adaptive D B S devices. Hypothetically, the D B S device functions through depolarization zone, synaptic-inhibition, melancholy like depression, and stimulus-inducedmodulations of patho-physiological networks movements thought the very focal method of activity.…”
Section: Uses Of Nbc and Deep Brain Stimulationsmentioning
confidence: 99%